A sale of books in Genoa in 1583 - Graziano Ruffini (JLIS.it, 2018)
The article, based on archival sources, examines a sale of books held in Genoa in 1583 between two booksellers: Cristoforo Zabata and Antonio Orero. Most of these books had been previously acquired in Venice. The article provides an accurate analysis of book prices according to subject: law, literature, history, medicine and so on. The survey also highlights costs with regard to the number of sheets, format and language, thus providing a set of information useful for further comparative cross-regional studies. The appendix includes a transcription of the source along with a bibliographic identification of the books enlisted.